2-Point Ultrasonography to Confirm Correct Position of the Gastric Tube in Prehospital Setting. Issue 9 (1st September 2014) - Brun, Pierre-Marie; Chenaitia, Hichem; Lablanche, Christophe; Pradel, Anne-Lise; Deniel, Cécile; Bessereau, Jacques; Melaine, Régis
ABSTRACT: X-ray remains the "gold standard" test to control the gastric tube (GT) position. The aim of this study is to estimate the diagnostic accuracy of a 2-point ultrasonography to confirm GT placement in the prehospital setting. Method: The emergency physician performed an ultrasound examination during GT insertion. The aim was to determine whether or not the GT could be viewed in the esophagus and/or in the stomach. Results: Thirty-two intubated patients were included. In 100% of cases, the GT was instantly identified by ultrasound at esophagus and in 62.5% at stomach. In 6 cases, the GT was not seen in the stomach, but the injection of air through the GT allowed to confirm intragastric position in 2 cases. In the 4 other cases, no dynamic fogging was observed. In hospital X-ray control confirmed the correct positioning of 28/32. Conclusion: The 2-point ultrasonographic live control of the GT position has a better sensitivity and a much higher specificity than the syringe test but similar to the xiphoid ultrasound control. However, our method allows to show the GT in the esophagus and to use the dynamic ultrasound fogging to reveal an intragastric position that was not obvious with the common techniques.